Online market entry: the motivations for imitation across retailer types - Bhatnagar, A.; Nikolaeva, R.; Ghose, S. (Managerial and Decision Economics, 2016)
This study examines the motivations for imitation in retailers' online channel entry. Extant literature suggests that legitimacy and efficiency are the primary motivators for firms to imitate. We develop hypotheses that center on the belief that not all firm types would use the same motivator for deciding to imitate and enter the online market; legitimacy would be the driving force for some retailer types whereas efficiency would be the motivator for others. We test our hypotheses on unique data collected from multiple sources. Our findings confirm that the motivators for imitation vary across retailer types